Heart rate variability and hemostatic parameters in patients with coronary heart disease and chronic heart failure - M. Z. Buy; A. Yu. Lebedeva; I. G. Gordeev; N. A. Volov; E. O. Taratukhin (Российский кардиологический журнал, 2013)
Aim. To assess the association between the changes in heart rate variability (HRV) and hemostatic parameters in patients with coronary heart disease (CHD) and chronic heart failure (CHF) as its complication. Material and methods. In total, 65 patients were examined at theO.M.FilatovCityClinicalHospital No. 15. The main group included 51 patients with CHD and CHF (35 men, 16 women; mean age 62Ѓ}6 years). The control group included 14 CHD-free patients with arterial hypertension (7 men, 7 women; mean age 56Ѓ}7 years). The examination included standard methods, plus the assessment of HRV and a wide range of coagulogram parameters. Results. CHD patients with CHF demonstrated the hyperactivation of sympathetic nervous system, which was manifested in increased LF/HF (up to 2,5 U), together with the suppression of parasympathetic activity (SDNNi decrease up to 39,1 ms; p<0,05). Circadian sympathetic-parasympathetic interactions were persistently disturbed, with increased sympathetic effects on cardiac rhythm and inadequately increased parasympathetic activity during nighttime (LF/HF circadian index 1,0Ѓ}0,5; p<0,001). The main group demonstrated a significant increase in protrombin index (83,4Ѓ}22,7% vs. 68,5Ѓ}11,23%; p<0,05), increased ADP-induced (0,5 μM) platelet aggregation (1,42Ѓ}0,45 U vs. 0,98Ѓ}0,42 U), and increased thrombin time (18,6Ѓ}6,4 vs. 12,9Ѓ}2,9; p<0,01). In CHD and CHF patients who had higher levels of sympathetic activation (LF/HF >2,0 U), protrombin time was reduced by 10,9%, while hematocrit was increased by 10,2%. In patients with elevated spontaneous platelet aggregation, increased sympathetic tone during nighttime was manifested in the reduction of mean cardiac interval duration (893,1Ѓ}111,5 ms vs. 982,7Ѓ}66,7 ms; p<0,05). The increase in nighttime sympathetic activation (nighttime LF/HF >2,0) was associated with a significant reduction (–20%) in ADP-induced platelet aggregation. Conclusion. Chronic pathological sympathetic hyperactivation in patients with CHD and CHF affects hemocoagulation parameters. Increased spontaneous platelet aggregation, reduced protrombin time, and elevated hematocrit, together with catecholamine-induced vasospasm, might increase the risk of thrombotic complications.